Literatur Reviewe : Pengaruh Penyuluhan Kesehatan terhadap Tingkat Pengetahuan Remaja tentang HIV/AIDS - Mike Susianti; Samsudin Ahmad Hasan (Universitas Gorontalo, 2022)
Abstract HIV-AIDS is one of the most feared diseases, because until now there has not been found a cure, so that people affected by the disease do not have a long life expectancy. The Purpos of the study was to find out the description snd relevant information about health education on the level of knowledge of adolescents about HIV-AIDS. The method in this study uses a descriptive narrative design with a literature review approach (literature study). The literature review study is a synthesis of the literature on the research topic. Sources of data used are derived from research journals that have been previously researched, this study uses 6 journals obtained from relevant databases, namely Google Scholar, IOS and Garuda from 2015 to 2020 . The results of the study based on the literature study used as comparison material was found that health education greatly influenced the level of knowledge of adolescents about HIV/AIDS. HIV/AIDS is a very dangerous disease, especially in adolescents, adolescents are always trying new things known, the low attention of adolescents about reproductive health, especially infectious diseases and also the lack of information or health education for adolescents so it is necessary to do health education about HIV/AIDS. Conclusion: There is an effect of health education on the level of knowledge of adolescents about HIV/AIDS.